Observations of one young and three middle-aged γ-ray pulsarswith the Gran Telescopio Canarias. Issue 1 (21st April 2018) - Mignani, R P; Testa, V; Rea, N; Marelli, M; Salvetti, D; Torres, D F; De Oña Wilhelmi, E
ABSTRACT: We used the 10.4 m Gran Telescopio Canarias to search for the optical counterparts to four isolated γ-ray pulsars, all detected in the X-rays by either XMM-Newton or Chandra but not yet in the optical. Three of them are middle-aged pulsars – PSR J1846+0919 (0.36 Myr), PSR J2055+2539 (1.2 Myr), PSR J2043+2740 (1.2 Myr) – and one, PSR J1907+0602, is a young pulsar (19.5 kyr). For both PSR J1907+0602 and PSR J2055+2539 we found one object close to the pulsar position. However, in both cases such an object cannot be a viable candidate counterpart to the pulsar. For PSR J1907+0602, because it would imply an anomalously red spectrum for the pulsar and for PSR J2055+2539 because the pulsar would be unrealistically bright ( r ′ = 20.34 ± 0.04) for the assumed distance and interstellar extinction. For PSR J1846+0919, we found no object sufficiently close to the expected position to claim a possible association, whereas for PSR J2043+2740 we confirm our previous findings that the object nearest to the pulsar position is an unrelated field star. We used our brightness limits ( g ′ ≈ 27), the first obtained with a large-aperture telescope for both PSR J1846+0919 and PSR J2055+2539, to constrain the optical emission properties of these pulsars and investigate the presence of spectral turnovers at low energies in their multiwavelength spectra.